Gastro-intestinal parasites of urban rhesus macaques (Macaca mulatta) in the Kathmandu Valley, Nepal - Asmita Adhikari; Narayan Prasad Koju; Babita Maharjan; Laxman Khanal; Milan Upreti; Randall C. Kyes (International Journal for Parasitology: Parasites and Wildlife, 2023)
Intestinal parasitic infections such as amoebiasis, ascariasis, hookworm infection, and trichuriasis are the most common infections among non-human primates (NHPs). There are always the possibilities of transmission these parasites between humans and NHPs. Multiple groups of rhesus macaques (Macaca mulatta) live in the urban area of Kathmandu Valley near human settlements, however the gastrointestinal (GI) parasitic infections in those macaques are understudied. This study aimed to explore the GI parasites in free-ranging macaques from Pashupatinath, Swayambhunath, Tripureshwor, Nilbarahi temples and a group of captive rhesus macaques in the Central Zoo, Kathmandu. Fecal samples were collected from the macaques between October 2021 to September 2022 and assessed for parasites by the both wet mount method and concentration technique. There is high prevalence of GI parasite infection; out of 121 fecal samples examined, 87.6% of samples were positive. Six species of protozoans and eight species of helminths were identified from the fecal samples including the first report of Iodamoeba butschlii in monkeys of Nepal. Among the protozoan parasites, Entamoeba coli (54.71%) showed the highest prevalence followed by Balantioides coli (44.33%), E. histolytica (19.81%), and Iodamoeba butschlii (10%). Among the helminths, Trichuris spp. (31.13%) and Strongyloides spp. (31.13%) showed the highest prevalence followed by Hookworm (24.52%), and Strongyle spp. (23.58%). The likelihood ratio test suggested that the prevalence differed significantly with the seasons for Iodamoeba butschlii, Giardia spp., Strongyles spp., Hookworm, and Trichostrongylus spp. The prevalence of E. histolytica, E. coli, Iodamoeba. butschlii, Trichuris spp., Trichostrongylus spp., and Unknown spp.1 differed with sampling localities. The high prevalence of GI parasites found in the macaques living in the densely urbanized Kathmandu presents a potential threat to humans and warrants further study as well as increased education of the public and management of the human-macaque interface in the urban landscape of the Valley.